PENYULUHAN DAN PENDAMPINGAN IBU HAMIL UNTUK PEMANTAUAN GERAK HARIAN JANIN MENGGUNAKAN KARTU DAN APLIKASI HAPPY TUMMY DI MENTENG, JAKARTA - Regina Vidya Trias Novita; Justina Purwarini Acihayati; Pratiwi H (Asawika : Media Sosialisasi Abdimas Widya Karya, 2023)
Monitoring the well-being of the fetus is an important part of managing pregnancy and childbirth, so it is necessary to carry out regular examinations of pregnant women and the fetus. These checks include checking the mother's weight, blood pressure, uterine fundal height, fetal heart rate and fetal movement in the uterus. All these are to prevent fetal death, although fetal death does not always occur in groups of high-risk pregnant women. Some deaths can actually occur in low-risk and even normal pregnancy groups.One way to solve the problems of pregnant women, especially pregnant women with a gestational age of more than 28 weeks in monitoring daily fetal movements, is to provide knowledge related to monitoring daily fetal movements as an effort to improve fetal well-being, and provide assistance in monitoring daily fetal movements which is facilitated by health personnels. Results of counseling and mentoring activities show that the average value of the mothers' knowledge has increased from 66.32 (pre-test) to 90.42 (posttest). 80% (35 mothers) monitored fetal movements routinely for 5 days and 20% (9 mothers) did not monitor routinely for 5 days. The average time it takes for a mother to feel 10 fetal movements is 8 hours. Providing education on how to widely monitor daily fetal movements is expected to increase the mothers’ ability to know the condition of the fetus they are carrying.